In Vivo Non-radioactive Assessment of mGlu5 Receptor-Activated Polyphosphoinositide Hydrolysis in Response to Systemic Administration of a Positive Allosteric Modulator - Zuena, Anna R.; Iacovelli, Luisa; Orlando, Rosamaria; Di Menna, Luisa; Casolini, Paola; Alemà, Giovanni Sebastiano; Di Cicco, Gabriele; Battaglia, Giuseppe; Nicoletti, Ferdinando (Frontiers in Pharmacology, 2018)
mGlu5 receptor-mediated polyphosphoinositide (PI) hydrolysis is classically measured by determining the amount of radioactivity incorporated in inositolmonophosphate (InsP) after labeling of membrane phospholipids with radioactive inositol. Although this method is historically linked to the study of mGlu receptors, it is inappropriate for the assessment of mGlu5 receptor signaling in vivo. Using a new ELISA kit we showed that systemic treatment with the selective positive allosteric modulator (PAM) of mGlu5 receptors VU0360172 enhanced InsP formation in different brain regions of CD1 or C57Bl mice. The action of VU0360172 was sensitive to the mGlu5 receptor antagonist, MTEP, and was abolished in mice lacking mGlu5 receptors. In addition, we could demonstrate that endogenous activation of mGlu5 receptors largely accounted for the basal PI hydrolysis particularly in the prefrontal cortex. This method offers opportunity for investigation of mGlu5 receptor signaling in physiology and pathology, and could be used for the functional screening of mGlu5 receptor PAMs in living animals.